2015
DOI: 10.1371/journal.pntd.0004234
|View full text |Cite
|
Sign up to set email alerts
|

Glycans from Fasciola hepatica Modulate the Host Immune Response and TLR-Induced Maturation of Dendritic Cells

Abstract: Helminths express various carbohydrate-containing glycoconjugates on their surface, and they release glycan-rich excretion/secretion products that can be very important in their life cycles, infection and pathology. Recent evidence suggests that parasite glycoconjugates could play a role in the evasion of the immune response, leading to a modified Th2-polarized immune response that favors parasite survival in the host. Nevertheless, there is limited information about the nature or function of glycans produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 67 publications
2
61
0
Order By: Relevance
“…In contrast, many of them inhibited TLR-induced DC maturation212223242540. However, as reported by Falcon and colleagues26, the inhibitory effect exerted by F. hepatica molecules could be reverted when treatment with LPS was delayed.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, many of them inhibited TLR-induced DC maturation212223242540. However, as reported by Falcon and colleagues26, the inhibitory effect exerted by F. hepatica molecules could be reverted when treatment with LPS was delayed.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, DCs from mice infected with F. hepatica have a semi-mature phenotype that is characterized by low MHC II and CD40 expression and high secretion of the immunoregulatory cytokine IL-1025. Given their remarkable capacity to present antigens to T cells, antigen-loaded DCs have been proposed as vaccines to prevent a spectrum of infectious diseases2627282930.…”
mentioning
confidence: 99%
“…VVL recognized molecular components with an apparent molecular weight pattern similar to that observed for hMGL (Figures 3B,C). Moreover, preincubation with the lectin VVL, but not ConA, two lectins that strongly interact with FhTE (10), inhibited the hMGL recognition, suggesting that VVL and hMGL interact with the same ligands present in FhTE (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Very recent reports3334, including our own32, have brought insights about the role of F. hepatica glycans in mediating the regulation of DC-maturation through CLR recognition. Our group has recently described that glycan structures produced by F. hepatica participate in the modulation of bone marrow-derived DCs (BMDCs) and induce/mediate the production of IL-10 and IL-4 during infection32.…”
mentioning
confidence: 95%
“…In addition, F. hepatica tegumental antigen modulates DC activity by suppressing MAPK-signaling and by up-regulating the expression of the suppressor of cytokine signaling 3 (SOCS3)31. Furthermore, we have demonstrated that DCs from mice infected with F. hepatica have a semi-mature phenotype that is characterized by low MHC II and CD40 expression and high secretion of the immunoregulatory cytokine IL-1032. Thus, it has been hypothesized that F. hepatica may modulate DC function and fate as a mean to control its pathogenesis and survival in the infected hosts.…”
mentioning
confidence: 99%